2011
DOI: 10.4067/s0717-95022011000400039
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Dentate Gyrus Astrocytes in Diabetic Rats: Protective Role of Urtica dioica

Abstract: GOLALIPOUR, M. J.; GHAFARI, S.; LATIFIMOGHADAM, M. H. & KABOLI, S.Alteration of dentate gyrus astrocytes in diabetic rats: Protective role of Urtica dioica. Int. J. Morphol., 29(4):1307-1312, 2011. SUMMARY:Diabetes mellitus can cause astrocytes alterations in the central nervous system. Urtica dioica (Nettle) is among several species listed for their use against diabetes in folk medicine. Therefore, this study was done to evaluate the protective effect of Urtica dioica on astrocytes density of the dentate gyru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
3
3
0
3
Order By: Relevance
“…The current work showed that the number of GFAP-positive astrocytes significantly increased in STZ-treated rats. This was in accordance with Golalipour et al (2011) and Selim and Selim (2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current work showed that the number of GFAP-positive astrocytes significantly increased in STZ-treated rats. This was in accordance with Golalipour et al (2011) and Selim and Selim (2013).…”
Section: Discussionsupporting
confidence: 90%
“…During reactive gliosis, astrocytes secrete neurotoxic substances such as inflammatory cytokines and free radicals, which actively attack protein molecules within neurons, resulting in neuronal damage, and contribute toward the pathogenesis of neurodegenerative diseases. These evidences indicate that altered astrocyte activity contributes toward the central nervous system pathophysiology in diabetes mellitus [9,39] .…”
Section: Discussionmentioning
confidence: 82%
“…The current work showed that the number of GFAP-positive astrocytes increased significantly in STZ-induced rats. Our result is similar to that of previous studies [31,32]. The alterations in astrocyte number are possibly because of oxidative stress [33] and free radical formation [34].…”
Section: Diabetic Group IIIsupporting
confidence: 93%
“…During reactive gliosis, astrocytes secrete neurotoxic substances such as inflammatory cytokines and free radicals, which actively attack protein molecules within neurons, resulting in neuronal damage, and contribute toward the pathogenesis of neurodegenerative diseases [36]. These evidences indicate that altered astrocyte activity contributes toward the CNS pathophysiology in DM [32].…”
Section: Diabetic Group IIImentioning
confidence: 98%
“…Diyabet tedavisi de en sık rastlanan kullanımlardan biridir(24). Bu sonuçlar ekstrenin hipoglisemik etkisinin beta hücre proliferasyonunu artırması ile bağlantılı olduğunu düşündürmektedir(53).Diabetes mellitus merkezi sinir sisteminde astrositlerde istenmeyen değişikliklere sebep olur. Bu amaçla streptozotosin ile indüklenen diyabetik sıçanlarda ısırganın astrositleri koruyucu etkinliği incelenmiştir.…”
unclassified